The Effect of Transformational Leadership Style on Perfomance and Satisfaction of MSME Employees Mediated Through Leader Member Exchange - M. Abdi Dzil Ikhram W; Rinaldy Achmad Roberth Fathoni (Universitas muhammadiyah malang, 2022)
The growth of Indonesia's economy depends significantly on micro, small, and medium-sized businesses (SMEs). When Indonesia experiences an economic crisis, SMEs become a powerful force that not only boosts national GDP but also helps to create jobs. This study's goal was to ascertain how the Leader Member Exchange, a kind of transformational leadership, affected worker productivity and job satisfaction. Partial Least Squares is a statistical test method used in this investigation (PLS). A questionnaire survey approach of data gathering was employed in this study. This study focuses on SMEs in East Java, one of which is that they have at least 50 individuals working for their company units. The study's findings show how transformational leadership affects worker performance. Additionally, there is no impact of transformative leadership on work satisfaction. The association between transformational leadership and employee performance is mediated by the Leader Member Exchange variable, although this variable does not mediate the relationship between transformational leadership and work satisfaction.